Incidence of graft failure with Achilles tendon allograft combined with RetroScrewTM tibial fixation in primary anterior cruciate ligament reconstruction. Issue 3 (May 2019) - Mantell, Matthew; Fox, Brad; Baker, Matthew; Kappa, Jason; Ho, Anthony; Pandarinath, Rajeev
Abstract : Background: The purpose of this study was to determine the failure rate of primary anterior cruciate ligament (ACL) reconstruction with low-dose irradiated Achilles tendon allograft by a single surgeon using Retroscrew TM (Arthrex, Naples, FL) tibial fixation. The same surgical technique, source for the allograft tissue, and postoperative rehabilitation were used. Methods: Fifty patients undergoing primary ACL reconstruction with Achilles tendon allograft from 2010-2012 were available with a minimum of 2-years of follow-up. Patients were excluded if they had undergone previous ipsilateral knee surgery. The mean age was 31.3 yr old at the time of surgery. Patients were evaluated with International Knee Documentation Committee (IKDC) scores, subjective instability, and return to sports at latest follow-up. Failure was defined as need for revision ACL reconstruction based on subjective symptoms, objective physical findings of laxity on Lachman examination, and evidence of re-tear on MRI. Results: Twelve of the 51 operative knees had reruptures with continued instability (23.5%). There was no significant difference between the age of patients with intact (31) and patients with re-rupture (32.1; P =0.317). Patients presented with graft failure at an average of 1.65 yr postoperatively. Conclusions: The results of our study showed an unacceptably high rate of failure of irradiated fresh frozen Achilles allograft for primary ACL reconstruction using tibial Retroscrew fixation.